Evaluation of Facial Aesthetic Changes in Growing Class II Patients Treated with Herbst or Elastodontics: A Retrospective Study - Domenico Ciavarella; Rossella Luciano; Mauro Lorusso; Angela Pia Cazzolla; Michele Laurenziello; Carlotta Fanelli; Silvia Caruso; Michele Tepedino (Dentistry Journal)
Objective: The objective of this study was to evaluate the facial profile changes of patients treated for class II skeletal malocclusions with an elastodontic appliance compared to those treated with the Herbst appliance and a control group. Methods: Forty class II patients were treated using an elastodontic appliance (Group EA) and were compared to 40 patients treated with the Herbst appliance (Group H) and to 40 untreated class II children (Group C). Aesthetic profile variables were analysed using Arnett’s analysis. Cephalograms were compared pre-treatment (T0) and post-treatment (T1). The Wilcoxon signed-rank test or paired-samples t-test was used for pairwise comparison of cephalometric measurements taken at T0 and T1. One-way ANOVA and Tukey’s post hoc test were performed to assess differences between the groups. Results: In the elastodontic group, the inclination of the upper incisors increased by 4.05°. In addition, the Pog–TVL and B–TVL distances decreased by 2.84 mm and 1.79 mm, respectively. In patients treated with an elastodontic appliance, the inclination of the upper incisors increased by 4.05°. In addition, the Pog–TVL and B–TVL distances decreased by 2.84 mm and 1.79 mm, respectively. In patients treated with the Herbst appliance, the inclination of the lower incisors increased by 6.11°. Furthermore, the treatment resulted in reductions in the Pog–TVL distance (2.58 mm), the B–TVL distance (2.26 mm), and the LL–TVL distance (2.31 mm). Conclusions: The profile changes achieved by both devices are favourable for correcting class II skeletal malocclusion.